Mar the cockatoo : a Boandik dreaming story. - South Australia. Education Department; South Australia. Education Department Aboriginal Education Team, Eastern Area. ([Adelaide, S. Aust.] : Education Dept. of South Australia, 1991)
Tells the story of how fire was made and teaches children about rules for living such as sharing within a group, caring for the environment and the native birds of the Lower South-East area of South Australia.
The unit was developed by members of the Eastern Area Aboriginal Education Team.
Designed to support teachers of the R-7 Aboriginal Studies Unit.
On title page: Years R-3.
Keywords: Aboriginal Australians -- Folklore -- Juvenile literature; Aboriginal Australians -- South Australia -- Folklore -- Juvenile literature; Birds -- South Australia -- Folklore; Ngarinyin language -- Juvenile literature; Language - Vocabulary - Word lists; Music - Vocal; Stories and motifs - Fire; Environment - Land management - Fire; Arabana / Arabunna people (L13) (SA SH53-03); Education - Primary - Curriculum; Stories and motifs - Birds; Arabana / Arabunna language (L13) (SA SH53-03); Education - Indigenous studies - Primary - Curriculum; Education - Teaching - Materials; Bungandidj / Buandig people (S13) (SA SJ54-06); Animals - Birds - Parrots; Education - Teaching; Language - Vocabulary - Animal names; Bungandidj / Buandig language (S13) (SA SJ54-06); South Australia (SA)